THE IMPACT OF INDUSTRIAL WORKERS WITH ISCHEMIC HEART DISEASE: LITERATURE REVIEW - Roni Al Faqih, Mohammad (Jurnal Ilmu Kesehatan MAKIA, 2024)
ABSTRACT Heart disease is common both in the general population but also in the working age population. However, the costs of cardiovascular disease (CVD) in the workplace are more difficult to measure but are likely to be just as high. Heart disease can be the most common cause of death including in company workers. This type of research is a literature review, analyzing journals published from 2018-2023 in accordance with PRISMA. The search was carried out using the PubMed database. There are ten journals that meet the inclusion criteria using PICOS analysis. Based on the ten journals that has been analyzed, There are several categories of these journals, including: heart disease category, gender category, shit schedule category and lifestyle which are risk factors for coronary heart disease in company workers. Cardiovascular diseases are the leading cause of death worldwide. It is important to not only consider the presence of workplace hazards such as exposure to noise (which has been linked to increased blood pressure) or carbon monoxide (which has been linked to increased rates of coronary artery disease), but then measure any potential hazards such as disease risk factors that industrial workers have, age and shift schedule.